Step
*
2
2
1
of Lemma
pair_support_double_sum
1. n : ℕ
2. m : ℕ
3. f : ℕn ⟶ ℕm ⟶ ℤ
4. x1 : ℕn
5. x2 : ℕn
6. y1 : ℕm
7. y2 : ℕm
8. (¬(x1 = x2 ∈ ℤ)) ∨ (¬(y1 = y2 ∈ ℤ))
9. ∀x:ℕn. ∀y:ℕm.  ((¬((x = x1 ∈ ℤ) ∧ (y = y1 ∈ ℤ))) 
⇒ (¬((x = x2 ∈ ℤ) ∧ (y = y2 ∈ ℤ))) 
⇒ ((f x y) = 0 ∈ ℤ))
10. ¬(x1 = x2 ∈ ℤ)
11. Σ(Σ(f x y | y < m) | x < n) = (Σ(f x1 y | y < m) + Σ(f x2 y | y < m)) ∈ ℤ
12. Σ(f x1 x | x < m) = (f x1 y1) ∈ ℤ
⊢ Σ(Σ(f x y | y < m) | x < n) = ((f x1 y1) + (f x2 y2)) ∈ ℤ
BY
{ ((InstLemma `singleton_support_sum` [m;f x2;y2] THENA Auto) THEN All ReduceSOAps) }
1
1. n : ℕ
2. m : ℕ
3. f : ℕn ⟶ ℕm ⟶ ℤ
4. x1 : ℕn
5. x2 : ℕn
6. y1 : ℕm
7. y2 : ℕm
8. (¬(x1 = x2 ∈ ℤ)) ∨ (¬(y1 = y2 ∈ ℤ))
9. ∀x:ℕn. ∀y:ℕm.  ((¬((x = x1 ∈ ℤ) ∧ (y = y1 ∈ ℤ))) 
⇒ (¬((x = x2 ∈ ℤ) ∧ (y = y2 ∈ ℤ))) 
⇒ ((f x y) = 0 ∈ ℤ))
10. ¬(x1 = x2 ∈ ℤ)
11. Σ(Σ(f x y | y < m) | x < n) = (Σ(f x1 y | y < m) + Σ(f x2 y | y < m)) ∈ ℤ
12. Σ(f x1 x | x < m) = (f x1 y1) ∈ ℤ
13. Σ(f x2 x | x < m) = (f x2 y2) ∈ ℤ
⊢ Σ(Σ(f x y | y < m) | x < n) = ((f x1 y1) + (f x2 y2)) ∈ ℤ
Latex:
Latex:
1.  n  :  \mBbbN{}
2.  m  :  \mBbbN{}
3.  f  :  \mBbbN{}n  {}\mrightarrow{}  \mBbbN{}m  {}\mrightarrow{}  \mBbbZ{}
4.  x1  :  \mBbbN{}n
5.  x2  :  \mBbbN{}n
6.  y1  :  \mBbbN{}m
7.  y2  :  \mBbbN{}m
8.  (\mneg{}(x1  =  x2))  \mvee{}  (\mneg{}(y1  =  y2))
9.  \mforall{}x:\mBbbN{}n.  \mforall{}y:\mBbbN{}m.    ((\mneg{}((x  =  x1)  \mwedge{}  (y  =  y1)))  {}\mRightarrow{}  (\mneg{}((x  =  x2)  \mwedge{}  (y  =  y2)))  {}\mRightarrow{}  ((f  x  y)  =  0))
10.  \mneg{}(x1  =  x2)
11.  \mSigma{}(\mSigma{}(f  x  y  |  y  <  m)  |  x  <  n)  =  (\mSigma{}(f  x1  y  |  y  <  m)  +  \mSigma{}(f  x2  y  |  y  <  m))
12.  \mSigma{}(f  x1  x  |  x  <  m)  =  (f  x1  y1)
\mvdash{}  \mSigma{}(\mSigma{}(f  x  y  |  y  <  m)  |  x  <  n)  =  ((f  x1  y1)  +  (f  x2  y2))
By
Latex:
((InstLemma  `singleton\_support\_sum`  [m;f  x2;y2]  THENA  Auto)  THEN  All  ReduceSOAps)
Home
Index